The Enormous Turnip - Illustrated by Johnson, Richard (London Ladybird Books)
One of Grandfather's turnips grows to such an enormous size that the whole family including the dog, cat, and mouse try in vain to pull it up.
Include Color Illustrations
Keywords: Turnips -- Cooperativeness